Antirepression function in Escherichia coli for the cAMP-cAMP receptor protein transcriptional activator. - Forsman, K (1992)
The cAMP receptor protein (CRP) complex (cAMP-CRP) is a global regulator of gene expression. It influences transcription from a number of promoters in Escherichia coli, including two divergently oriented promoters in the pap pili-adhesin gene system. To further define the role of cAMP-CRP in pap regulation we monitored protein-DNA interactions in vitro and levels of pap transcription in vivo in wild-type and mutant pap-containing clones. The results showed that activation was mediated by a single cAMP-CRP-binding site centered at nucleotide positions -215.5 and -115.5 relative to the transcriptional start points. A target for the pap-specific regulatory protein PapB was localized adjacent to the cAMP-CRP-binding site. The long-range effects exerted from the protein-binding sites were consistent with the idea that cAMP-CRP caused a change in the local DNA conformation and that a nucleoprotein complex (involving cAMP-CRP and PapB) was formed in the region between the pap promoters. Moreover, transcription became independent of activation of cAMP-CRP and the PapB protein in a mutant lacking the nucleoid-associated protein H-NS. Our findings suggest that the cAMP-CRP complex mediates its positive regulatory function by alleviating transcriptional silencing and, as such, plays a role as antirepressor.